2007
DOI: 10.1016/j.jalz.2007.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of the diagnosis of dementia

Abstract: Most ethical guidelines strongly promote disclosure of a diagnosis of dementia to the affected individual, based on the principle of autonomy. Nevertheless, codes of medical ethics allow for various interpretations of this issue and surveys of clinical practice illustrate that such disclosure is by no means the rule. We argue that diagnostic disclosure for persons with dementia must be considered a process that begins when cognitive impairment is first suspected and that evolves over time as information is obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…We chose this situation because 1) diagnostic conversations involve both information giving and receiving and are likely to evoke expressions of power [1], and 2) the delivery of a diagnosis is a critical moment in dementia care, when dominance can set the tone for future interactions [12]. We studied two linguistic manifestations of power.…”
Section: Introductionmentioning
confidence: 99%
“…We chose this situation because 1) diagnostic conversations involve both information giving and receiving and are likely to evoke expressions of power [1], and 2) the delivery of a diagnosis is a critical moment in dementia care, when dominance can set the tone for future interactions [12]. We studied two linguistic manifestations of power.…”
Section: Introductionmentioning
confidence: 99%
“…Some older citizens have expressed concerns about being labeled cognitively impaired (8) and some people with a diagnosis of dementia have found it distressing and stigmatising (7,(9)(10)(11)(12). However, the perspectives of older people at risk of becoming "a person with dementia" and of people with dementia have been significantly neglected in empirical research (7,13,14). Recently, older patients' attitudes towards dementia screening were measured in primary care clinics in the United States and the United Kingdom (15).…”
Section: Introductionmentioning
confidence: 99%
“…4 from the section on ethical issues in dementia -disclosure, www.cccdtd.ca). 5 Disclosure can lead to an open dialogue between the patient, his or her family or caregiver, and health care providers about a number of important issues such advance planning, the option of pharmacotherapy and research participation. Although the potential for an adverse psychological reaction is often used as justification not to disclose the diagnosis, a recent study found that this was not the case for most patients and caregivers.…”
Section: Disclosure Of the Diagnosis And Decision-makingmentioning
confidence: 99%
“…The question is not "if" the diagnosis of dementia should be disclosed but rather "how" and "when" to do so. 5 Disclosure has been identified by primary care physicians as a particularly difficult aspect of dementia care. 19 Unfortunately there is little research on how disclosure of a dementia diagnosis is actually managed in clinical practice.…”
Section: Disclosure Of the Diagnosis And Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation